Effect of the At-CDC27a gene on Nicotiana benthamiana phenotype and accumulation of recombinant proteins - Kopertekh, Lilya; Reichardt, Sven (Frontiers in Plant Science, 2022)
In this study the anaphase promoting complex subunit CDC27a from Arabidopsis thaliana was introduced in the genome of Nicotiana benthamiana by Agrobacterium tumefaciens. The presence of the At-CDC27a gene facilitates plant biomass production. Compared to wild type N. benthamiana the leaf mass fraction of the best performing transgenic line At-CDC27a-29 was increased up to 154%. The positive effect of the At-CDC27a expression on leaf biomass accumulation was accompanied by an enlarged total leaf area. Furthermore, the ectopic expression of the At-CDC27a also affected cellular conditions for the production of foreign proteins delivered by the TRBO vector. In comparison to the non-transgenic control, the protein accumulation in the At-CDC27a-29 plant host increased up to 146% for GFP and up to 181% for scFv-TM43-E10. Collectively, the modified N. benthamiana plants developed in this study might be useful to improve the yield of recombinant proteins per biomass unit in closed facilities.